Hepatoprotective and in vitro antioxidant effects of native depolymerised-exopolysaccharides derived from Termitomyces albuminosus - Huajie Zhao (Nature Portfolio, 2017)
Abstract In this study, native depolymerised-exopolysaccharides (DEPS) were successfully derived from the exopolysaccharides (EPS) of Termitomyces albuminosus, and its hepatoprotective effects against a high-fat emulsion and in vitro antioxidant activities were investigated. Based on the results of in vitro assays, DEPS showed superior antioxidant activities compared with EPS dose-dependently. According to the in vivo assays both EPS and DEPS significantly decreased the lipid levels, improved the enzymatic activities, and reduced lipid peroxidation in both serum and hepatic homogenates. Furthermore, EPS and DEPS attenuated the high-fat emulsion-induced histopathological injury to the liver. Both EPS and DEPS might be used as natural drugs to treat and protect against hyperlipidaemia and liver injury induced by a high-fat emulsion. In addition, based on the results of GC and HPLC analyses, rhamnose and low molecular weight compounds may play an important role in contributing to the antioxidant activities of EPS and DEPS.